A review of eye tracking for understanding and improving diagnostic interpretation. - Brunyé, Tad T.; Drew, Trafton.; Weaver, Donald L.; Elmore, Joann G. (Tufts University. Tisch Library., 2019)
Abstract: Inspecting digital imaging for primary diagnosis introduces perceptual and cognitive demands for physicians tasked with interpreting visual medical information and arriving at appropriate diagnoses and treatment decisions. The process of medical interpretation and diagnosis involves a complex interplay between visual perception and multiple cognitive processes, including memory retrieval, problem-solving, and decision-making. Eye-tracking technologies are becoming increasingly available in the consumer and research markets and provide novel opportunities to learn more about the interpretive process, including differences between novices and experts, how heuristics and biases shape visual perception and decision-making, and the mechanisms underlying misinterpretation and misdiagnosis. The present review provides an overview of eye-tracking technology, the perceptual and cognitive processes involved in medical interpretation, how eye tracking has been employed to understand medical interpretation and promote medical education and training, and some of the promises and challenges for future applications of this technology.; Keywords: Eye tracking, Medical informatics, Visual perception, Visual search, Medical decision-making.; Springer Open.